On the Malaysian ringgit exchange rate determination and recent depreciation - Quadry, Mahmud Oluwaseyi; Mohamad, Azhar; Yusof, Yusniliyana (IIUM Press, International Islamic University Malaysia, 2017)
The Ringgit (MYR) has recently, since October 2015, suffered a large decline against most world currencies. In this study, based on the theory of exchange rate determination, we tested for a long run relationship between both MYRUSD and MYRGBP against the differential interest rate, differential money supply, price of world crude oil and Goods and Services Tax (GST, as dummy variable). We ran an Autoregressive Distributive Lag (ARDL) model on monthly data from January 2010 to January 2017. We found a negative long run relationship between MYRGBP and differential money supply and a positive long run relationship against the world crude oil price. As the Ringgit (MYR) supply increased relative to the British Pound, the Ringgit depreciated, and as the crude oil price strengthened, the Ringgit appreciated. A high dependency of the Ringgit on world crude oil implies a bad sign. In our view, Malaysia needs to work harder to attract foreign direct investment to maintain the value of the Ringgit at a healthy level.